Persentuhan Kiai Lokal Dalam Kontestasi Politik Era Reformasi Di Madura: Tinjauan Sejarah - Topan, Ali; Tianah, Itaanis (Jurnal Keislaman, 2024)
This study explores the role of local Kiai of Madura in the politics of the reform era, examining their contribution to practical political contestation and its impact on the Muslim-majority Madura community. Kiai, who was respected and had great influence, exercised the role of religious figure and public official. The local Kiai here refers to Kiai who are directly involved in the world of practical politics. The purpose of this study is to analyze the contribution of Kiai in Madura politics and its impact on the policy and application of the teachings of Ahlus Sunnah Wal-Jamaah. This research is a literature review using the historical method with four steps. First heuristic (collection of sources), primary and secondary sources used in the form of books, scientific articles, proceedings, the results of the data on votes obtained from the KPU and the writings that are relevant to this research obtained from the National Library of Indonesia, UIN Jakarta Library, Google Scholar, Sinta and observations in the field. Second, source criticism. Third, interpretation and finally historiography. As an analytical knife, the research uses the hegemonic theory of Gramsci. The findings show that Kiai plays an important role in legal and policy politics, fighting for people's rights and grounding religious teachings. This research provides insight into the integration of religious teachings with public interest in the context of reform.